A strengths-based data capture model: mining data-driven and person-centered health assets. Issue 1 (24th May 2018) - Gao, Grace; Kerr, Madeleine J; Lindquist, Ruth A; Chi, Chih-Lin; Mathiason, Michelle A; Austin, Robin R; Monsen, Karen A
Abstract: With health care policy directives advancing value-based care, risk assessments and management have permeated health care discourse. The conventional problem-based infrastructure defines what data are employed to build this discourse and how it unfolds. Such a health care model tends to bias data for risk assessment and risk management toward problems and does not capture data about health assets or strengths. The purpose of this article is to explore and illustrate the incorporation of a strengths-based data capture model into risk assessment and management by harnessing data-driven and person-centered health assets using the Omaha System. This strengths-based data capture model encourages and enables use of whole-person data including strengths at the individual level and, in aggregate, at the population level. When aggregated, such data may be used for the development of strengths-based population health metrics that will promote evaluation of data-driven and person-centered care, outcomes, and value.